2012
DOI: 10.3319/tao.2011.06.20.02(aa)
|View full text |Cite
|
Sign up to set email alerts
|

Simulation in the Front Region of the Earth’s Magnetosphere

Abstract: A laboratory experiment was conducted to investigate the interaction between a plasma beam and a magnetic dipole, simulating the interaction between the solar wind and magnetized planets. The emphasis in this paper is on the laboratory simulation in the front region of the Earth's magnetosphere and their variation under different solar wind conditions. The boundary in the front region of the magnetosphere is observed in a space simulation laboratory and the magnetospheric structure is produced by a super-Alfvé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…And the information of the aurora and radiation belt is observed for the first time in the UCR-T1 experiments. The topology and the flank position of the Earth's magnetopause have been investigated in previous paper (Yur et al 1995(Yur et al , 1999(Yur et al , 2012. The laboratory simulation of magnetosphere for dipole tilts is also a first trial in UCR-T1 experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And the information of the aurora and radiation belt is observed for the first time in the UCR-T1 experiments. The topology and the flank position of the Earth's magnetopause have been investigated in previous paper (Yur et al 1995(Yur et al , 1999(Yur et al , 2012. The laboratory simulation of magnetosphere for dipole tilts is also a first trial in UCR-T1 experiments.…”
Section: Discussionmentioning
confidence: 99%
“…1d. The details of the experimental setup and scaling have been previously described in (Rahman et al 1989(Rahman et al , 1991Birn et al 1992;Yur et al 1995Yur et al , 2012.…”
Section: Derived Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Yur et al 1999) the x-point was observed in the tail when a southward field was applied. A study of the front region of a magnetosphere (Yur et al 2012) revealed that, in fact, a region of opposite southward field does not exist upstream of the magnetopause. Thus, while authors claim that an external magnetic field partially penetrates into plasma, this is not supported by the data so far presented.…”
Section: Plasma Physics and Controlled Fusionmentioning
confidence: 99%